2022
DOI: 10.6004/jnccn.2021.7047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Allocation on Survival During Intermittent Chemotherapy Shortages: A Modeling Analysis

Abstract: Background: Intermittent shortages of chemotherapeutics used to treat curable malignancies are a worldwide problem that increases patient mortality. Although multiple strategies have been proposed for managing these shortages (eg, prioritizing patients by age, scarce treatment efficacy per volume, alternative treatment efficacy difference), critical clinical dilemmas arise when selecting a management strategy and understanding its impact. Patients and Methods: We developed a model to compare the impact of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…While current research is evaluating strategies to manage these drug shortages, 6 better, more enduring solutions are required to ensure that all patients have access to the medicines they need. In what follows, we examine differing policies and explore better ways to balance public health needs in times of uncertainty or crisis and to ensure an appropriate supply of critical medicines, as well as medicines with vulnerable supply chains, that are crucial to the everyday lives and well-being of patients.…”
mentioning
confidence: 99%
“…While current research is evaluating strategies to manage these drug shortages, 6 better, more enduring solutions are required to ensure that all patients have access to the medicines they need. In what follows, we examine differing policies and explore better ways to balance public health needs in times of uncertainty or crisis and to ensure an appropriate supply of critical medicines, as well as medicines with vulnerable supply chains, that are crucial to the everyday lives and well-being of patients.…”
mentioning
confidence: 99%
“…2 Postapproval dose optimization methodologies that illuminate a drug's true dose-response curve may be useful in the future to reduce the morbidity and mortality of drug scarcity, as well as individual and societal financial toxicity. [18][19][20] Most importantly, however, a more patient-centered approach to dosing is favored not only by patients but also by many oncologists. 21 Taken together, the motivation for postapproval dose optimization is clear but its priorities need defining.…”
mentioning
confidence: 99%
“…In this issue of JNCCN, Hantel et al 7 describe a hospital-level model constructed to compare effects of different chemotherapy allocation strategies on patient survival using vincristine as an example. Using an institutional database and survival probabilities from NCCN Guidelines, a model was constructed and validated to determine survival outcomes across varying levels of vincristine shortages, testing different prioritization strategies.…”
mentioning
confidence: 99%
“…Using an institutional database and survival probabilities from NCCN Guidelines, a model was constructed and validated to determine survival outcomes across varying levels of vincristine shortages, testing different prioritization strategies. Hantel et al 7 found that an efficacy-per-volume prioritization strategy significantly improved projected survival. The model operates on the principle of maximizing survival and was successful in testing different allocation strategies and demonstrating that the choice of allocation strategy can impact patient survival based on real-world data.…”
mentioning
confidence: 99%
See 1 more Smart Citation